2003
DOI: 10.1046/j.1439-0442.2003.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inter‐ and Intra‐Observer Variability on Echocardiographic Measurements in Awake Cats

Abstract: The objective of this study was to determine intra- and inter-observer variability of echocardiographic measurements in awake cats. Four observers with different levels of experience in echocardiography performed 96 echocardiographic examinations in four cats on four different days over a 3-week period. The examinations were randomized and blinded. The maximum within-day and between-day CV values were 17.4 and 18.5% for inter-ventricular septal thickness in diastole, 18.7 and 22.6% for left ventricular free-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 12 publications
8
94
2
1
Order By: Relevance
“…Our results show that the repeatability and reproducibility of the AMM technique in the awake BN are adequate for both research and routine clinical use: 90% and 80% of the within-and between day CV values were <15% and 10% respectively, which indicates a good to excellent variability of most of the AMM measurements. 20,21 These CV values are similar to those obtained in unsedated small animals using standard M-mode TTE. 20,21 Although AMM may be affected by 2D echocardiography limitations, i.e., lower frame rate as compared to standard M-mode, recent advances in digital imaging technology have led to increased 2D frame rates of up to 250 frames/s, thus providing reconstruction of good quality M-mode images, similar to those obtained in BN in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results show that the repeatability and reproducibility of the AMM technique in the awake BN are adequate for both research and routine clinical use: 90% and 80% of the within-and between day CV values were <15% and 10% respectively, which indicates a good to excellent variability of most of the AMM measurements. 20,21 These CV values are similar to those obtained in unsedated small animals using standard M-mode TTE. 20,21 Although AMM may be affected by 2D echocardiography limitations, i.e., lower frame rate as compared to standard M-mode, recent advances in digital imaging technology have led to increased 2D frame rates of up to 250 frames/s, thus providing reconstruction of good quality M-mode images, similar to those obtained in BN in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…20,21 These CV values are similar to those obtained in unsedated small animals using standard M-mode TTE. 20,21 Although AMM may be affected by 2D echocardiography limitations, i.e., lower frame rate as compared to standard M-mode, recent advances in digital imaging technology have led to increased 2D frame rates of up to 250 frames/s, thus providing reconstruction of good quality M-mode images, similar to those obtained in BN in the present study. 8,11 Sklansky et al demonstrated that the TTE image quality in adult BN was not improved by breath holding.…”
Section: Discussionsupporting
confidence: 80%
“…Chetboul and collaborators also reported a marked withinday and between-day intra-and inter-observer variability according to the observers' experience, and its influence on conventional echocardiographic measurements in the cat. 18 In the present study, the cats were deliberately screened in a single cardiologic center involving validated observers and methods so as to limit the influence of intra-and inter-observer variability. Using this diagnostic protocol, the prevalence of HCM in Maine Coon cats with a mean age of 3 years was shown to be less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…16 Only one imaging center was utilized in order to limit the bias in echocardiographic measurements induced by inter-observer variability. 18 Pathological hypertrophy was defined as a diastolic LVFW or IVS thickness !6 mm using 2D or M-mode echocardiography. 1e3 In cats >4 years old with an LV hypertrophic pattern, HCM was diagnosed after excluding both systemic arterial hypertension (systolic arterial blood pressure <160 mmHg in unstressed cats) and hyperthyroidism (total thyroxin plasma levels [T4], reference interval: 10e50 nmol/L).…”
Section: Animalsmentioning
confidence: 99%
“…26 LV enddiastolic and end-systolic diameters, LVFW thickness and IVS thickness in diastole and in systole were measured by use of the 2D-guided M-mode 27 in accordance with the recommendations of the American Society of Echocardiography, 28 and the LV fractional shortening (%FS) was calculated.…”
Section: Conventional Echocardiography and Dopplermentioning
confidence: 99%